Model Kolaborasi Basarnas dan Dinas Sosial dalam Penanggulangan Bencana di Kabupaten Kolaka - Iswani Mujiarti; Ashari; Rahmat Hidayat (PENA BANGSA: Bisnis dan Tata Kelola Publik Adaptif, 2025)
Disaster management at the regional level requires cross-agency collaboration because each institution holds different roles, authorities, and capacities. In Kolaka Regency, Basarnas is responsible for search and rescue (SAR) operations, while the Social Service handles logistics provision, evacuation shelters, and fulfillment of basic needs for survivors. The complexity of disasters demands synergy between these institutions to ensure faster, more effective, and well-coordinated responses. This study aims to analyze the forms of collaboration between Basarnas and the Social Service in disaster management in Kolaka Regency and to identify the dominant collaboration model based on the Agranoff–McGuire theory. The research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. Informants consisted of eight individuals from Basarnas, the Social Service, and the Regional Disaster Management Agency (BPBD). Data were analyzed using data reduction, data presentation, and conclusion drawing techniques. The findings show that the collaboration between Basarnas and the Social Service functions effectively and complements the main duties of each institution. Collaboration occurs during the mitigation stage (preparedness drills, outreach, and simulations), emergency response (evacuation, logistics distribution, establishment of public kitchens), and early recovery (needs assessment for survivors). Analysis based on the Agranoff–McGuire framework reveals that the Contented Model is the dominant form of collaboration, although elements of other models—such as Jurisdiction-Based, Top-Down, Donor–Recipient, and Reactive Models—are also evident in practice. Collaboration between Basarnas and the Social Service in Kolaka Regency enhances responsiveness, efficiency, and coordination in disaster management, even as both institutions continue to operate within their respective jurisdictions. The resulting collaboration is adaptive, strategic, and oriented toward field needs, thereby strengthening regional capacity in disaster risk reduction.